Development of Nasal Mucoadhesive Microspheres of Granisetron: A Potential Drug - Pandey, Jaideo; Shankar, Ravi; Kumar, Manish; Shukla, Kuldeep; Kumari, Beena (Drug Research, 2020)
Background Granisetron is a serotonin 5-HT3 receptor antagonist used as an antiemetic to treat nausea and vomiting following chemotherapy and radiotherapy. Its main effect is to reduce the activity of the vagus nerve, which is a nerve that activates the vomiting center in the medulla oblongata.Objectives In this research mucoadhesive microspheres were developed in order to carry out the absorption of drug through nasal mucosa with the aim to improve therapeutic efficacy, avoid hepatic first pass metabolism and increase residence time.Material and Methods Mucoadhesive microspheres of Granisetron using chitosan as polymer were prepared by emulsification cross-linking method to increase the residence time on the mucosa. The surface of prepared microspheres was characterized by SEM (Scanning electron microscopy) and evaluated for particle size, encapsulation efficiency, production yield, swelling ability, in-vitro mucoadhesion, in-vitro drug release and stability study.Result Among all the formulations F6 with drug/polymer ratio of 1:3 displayed the best result. On drug release kinetic model study, all the formulations follow Zero order. Stability studies revealed that the microspheres kept at 25±2°C and 60±5% RH showed the maximum stability.Conclusion After all the evaluation parameters and result obtained it can be said that these results confirmed the suitability of Granisetron mucoadhesive chitosan microspheres for nasal delivery system.
Keywords: drug delivery; pharmaceutics; pharmacokinetics